PERSEPSI MAHASISWA ATAS KEGUNAAN DAN KEMUDAHAN TEKNOLOGI TERHADAP ADOPSI TEKNOLOGI ARTIFICIAL INTELLIGENT (AI) DALAM AKUNTANSI - Nelly Prima Putri (Ensiklopedia of Journal, 2026)
This study aims to examine students' perceptions of the usefulness and ease of use of technology in relation to the adoption of Artificial Intelligence (AI). This study used purposive sampling, with students currently pursuing a bachelor's degree in accounting at Universitas Putra Indonesia YPTK Padang as the sample. The analysis method used was multiple regression, using SmartPLS 3 as the analytical tool with the SEM PLS model. The results showed that: 1) Perceptions of the usefulness of technology influence the intention to adopt technology; 2) Perceptions of the ease of use of technology influence the intention to adopt technology.Keywords: Technology Adoption, Artificial Intelligence, Technology Usefulness